Virtual 3D Urban Landscape Design Taman Kota Berbasis Teknologi Komputer Grafis - Edy Jogatama Purhita; AnthoniusTyas Adi Pratama; Erwan Nur Hidayat (STEKOM PRESS, 2021)
Urban landscape design is an approach in designing cities that has a positive impact on city residents by providing a livable environment. Urban landscapes come in various forms, one of which is city parks. A city park is one of the facilities provided by a city and its residents can carry out several activities in it. A city park also serves as a city landmark. The city of Salatiga has several parks with recreational functions but not many city parks are available to function as public spaces. One of them is a park located in Tingkir District, Salatiga City, namely Tingkir Park. The purpose of this study was to apply 3D computer technology in the redesign of Tingkir park with the concept of Urban landscape design. A city park that is functional, aesthetically pleasing, can be a better public space and can become a landmark in the area. The method of developing a Virtual 3D City Park Design product uses 5 steps ADDIE (Analysis, Design, Development, Implement and Evaluation). In academic interest, this research results in the experimentation of computer graphics technology in the development of urban park design.